Examining Differences in Health-Related Technology Use between Millennial and Older Generations of Caregivers - Virginia T. Gallagher; Shannon E. Reilly; David Martin; Carol Manning; Kelly M. Shaffer (Nursing Reports)
Background/Objective: Caregivers from the Millennial generation are an emerging and understudied group of unpaid care providers in America who may benefit from digitally delivered support. To inform the design/tailoring of interventions for this group, we aimed to understand how Millennials may differ from other generations of caregivers regarding digital health-related technology use. Methods: Using the Health Information National Trends Survey (HINTS), Version 6, we conducted a cross-sectional study comparing health technology access and use across four generations of unpaid caregivers (n = 545; Millennials, Gen X, Baby Boomers, and Silent Generation) of adults with chronic conditions using chi-square and Kruskal–Wallis non-parametric tests. Results: Compared to Baby Boomer and Silent Generation caregivers, Millennial caregivers more frequently reported having a cellular internet connection, using a wearable activity device, a health/wellness mobile application, choosing telehealth appointments for convenience, and most frequently used social media in general and to view health-related videos (ps < 0.005). Additionally, Millennials were more likely to report possessing a smartphone (compared to Gen X and Silent Generation) and more frequently used social media for peer interaction about health (compared to all older generations; ps < 0.005). Conclusion: Millennials differ from older generations of caregivers regarding health-related technology access and use, which may have implications for intervention design and tailoring.